PENGARUH DIMENSI KEPEMIMPINAN TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH MOTIVASI: STUDY PADA PT JANU PUTRA SEJAHTERA - Irda Aan Setyawan; Wahyu Purwanto (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This research is to analyze the effect dimensions of leadership to employees mediated by the motivation of research at PT. Janu Putra Sejahtera. In this study the population of the company PT. Janu Putra Sejahtera with the criteria of being a permanent employee or having worked more than 1 year. From the predetermined assessment, there were 216 employees. The sampling technique uses a purposive sampling technique of 80 respondents. The method of data collection uses a questionnaire method with a Likert scale. The data analysis technique used is path analysis. The results of the study show that Motivation (Y1) acts as a mediator between interpersonal roles (X1) of leaders and employee performance (Y2). This is evidenced by the indirect coefficient value of 0.132 greater than the direct coefficient value of 0.113. The results also prove that Motivation (Y1) acts as a mediator between the role of informational (X2) leaders and employee performance (Y2). This is evidenced by the indirect effect coefficient of 0.299 greater than the direct coefficient value of 0.198. Motivation (Y1) acts as a mediator between decisional roles (X3) of leaders and employee performance (Y2). This is evidenced by the indirect coefficient value of 0.249 greater than the direct coefficient value of 0.164. From the results of this study it can be concluded that through motivation, the role of dimensions will be more effective in improving the performance of employees of PT. Janu Putra Sejahtera.